2004
DOI: 10.1038/sj.leu.2403544
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of the MAPkinase p38 is critical for MMP-9 production and survival of B-CLL cells on bone marrow stromal cells

Abstract: In the present work we investigated the role and biological significance of mitogen activated protein kinases (MAPK) in Bcell chronic lymphocytic leukaemia (B-CLL). The MAPK p38 was constitutively activated in B-CLL, but not in normal peripheral B cells. In addition, we demonstrated that the upstream kinases of p38, MKK3/6 were also constitutively activated in B-CLL cells. Furthermore, we determined by EMSA that the p38 MAP kinase pathway was not linked to the constitutive high expression of NF-jB, a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 38 publications
(35 reference statements)
7
47
0
2
Order By: Relevance
“…Our observations strengthen the notion that p38, a known regulator of stress responses, also regulates directed migration (32). Interestingly, p38 MAPK has been shown to be constitutively active in CLL, where it regulates MMP-9 production, suggesting a role in invasion (34). We report here that p38 activation is further increased upon CLL19 exposure in CIP4-depleted CLL cells, suggesting that control of its activation is important in regulating migration.…”
Section: Discussionsupporting
confidence: 76%
“…Our observations strengthen the notion that p38, a known regulator of stress responses, also regulates directed migration (32). Interestingly, p38 MAPK has been shown to be constitutively active in CLL, where it regulates MMP-9 production, suggesting a role in invasion (34). We report here that p38 activation is further increased upon CLL19 exposure in CIP4-depleted CLL cells, suggesting that control of its activation is important in regulating migration.…”
Section: Discussionsupporting
confidence: 76%
“…24 Our results confirmed the previously published data demonstrating that p38 MAPK is constitutively active and exerts a protective role in CLL. 32 We cannot totally exclude that IL-24 works also through a p38MAPK-independent mechanism; however, our data suggested a competition between IL-24 and SB 203580 for p38 MAPK activation as evidenced by sequential incubations. Indeed, IL-24 augmented p38 MAPK phosphorylation when added several hours after SB 203580, suggesting that the inhibitory effect of this drug is reversible (data not shown).…”
Section: Discussionmentioning
confidence: 41%
“…Recently, it was reported that the constitutive expression of MMP-9 in B-CLL cells depends on p38 MAP kinase activity, and that the survival of B-CLL cells on stroma is impaired upon inhibition of p38 or MMP-9 activity. 34 This indicates that MMP-9, in addition to its effect on angiogenesis, contributes to the well-known survival of leukemic cells in a bone marrow stroma microenvironment. Therefore, the blockade of MMP-9 production could also antagonize the antiapoptotic effect of stromal cells in vivo in B-CLL patients.…”
Section: Discussionmentioning
confidence: 99%